2013
DOI: 10.1371/journal.pone.0059012
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-Induced Mitochondria Alterations and Inflammation in Brain and Insulin-Responsive Cells

Abstract: BackgroundMetabolic syndrome (MetS) is a constellation of factors including abdominal obesity, hyperglycemia, dyslipidemias, and hypertension that increase morbidity and mortality from diabetes and cardiovascular diseases and affects more than a third of the population in the US. Clozapine, an atypical antipsychotic used for the treatment of schizophrenia, has been found to cause drug-induced metabolic syndrome (DIMS) and may be a useful tool for studying cellular and molecular changes associated with MetS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 50 publications
(84 reference statements)
2
48
0
Order By: Relevance
“…Finally, in this study, we assessed the short-term effect of clozapine (over 2 to 3 days), but not the long-term effect. Although the dose of clozapine that we used was rational and has been implemented in many studies [22,42,43], we also demonstrated that even at a lower concentration, clozapine continued to impair NSCLC cell growth during treatment for a longer period. Not only is this finding consistent with the clinical observation that patients with schizophrenia require prolonged antipsychotic administration [24], but the dose that we used for long-term treatment was also closer to the actual dose used in the clinic [44,45].…”
Section: Discussionmentioning
confidence: 92%
“…Finally, in this study, we assessed the short-term effect of clozapine (over 2 to 3 days), but not the long-term effect. Although the dose of clozapine that we used was rational and has been implemented in many studies [22,42,43], we also demonstrated that even at a lower concentration, clozapine continued to impair NSCLC cell growth during treatment for a longer period. Not only is this finding consistent with the clinical observation that patients with schizophrenia require prolonged antipsychotic administration [24], but the dose that we used for long-term treatment was also closer to the actual dose used in the clinic [44,45].…”
Section: Discussionmentioning
confidence: 92%
“…Streptomycin administration linked with G1555A mutation results in ototoxicity and deafness [89]. Further, clozapine treatment may give rise to increased production of pro-inflammatory cytokines involved in inflammation, which in turn is associated with alterations in mitochondrial function and obesity [95] (Table 1, 2). The antidiabetic drug metformin was found to inhibit OXPHOS by directly targeting the ETC, thus acting as a mitochondrial inhibitor as well as inducing lactic acidosis [96,97].…”
Section: Mitochondrial Dna Mutations Associated With Antibioticsmentioning
confidence: 99%
“…Although there is insufficient evidence for the association between elevated inflammatory markers and the etiopathology of schizophrenia (Manu et al, 2014), proinflammatory mediators and inflammation are well known to negatively affect the metabolism of glucose and to induce insulin resistance and T2DM (Contreras-Shannon et al, 2013). Interestingly, atypical antipsychotics induce the transcription factor nuclear factor-κB (NF-κB) and NF-κB target genes such as the proinflammatory cytokines TNF-α, IL-1β, IL-8 and monocyte chemoattractant protein-1 (MCP-1) in human adipocytes (Sarvari et al, 2014).…”
Section: Antipsychotics Glucose Intolerance Insulin Resistance and mentioning
confidence: 99%
“…Interestingly, atypical antipsychotics induce the transcription factor nuclear factor-κB (NF-κB) and NF-κB target genes such as the proinflammatory cytokines TNF-α, IL-1β, IL-8 and monocyte chemoattractant protein-1 (MCP-1) in human adipocytes (Sarvari et al, 2014). In addition, atypical antipsychotics increase the secretion of proinflammatory cytokines by rat adipocytes (Contreras-Shannon et al, 2013), and the secretion of both IL-8 and MCP-1 by human adipocytes (Sarvari et al, 2014). Elevated levels of MCP-1 can potentially induce monocytes/macrophages recruitment into the adipose tissue, which can in turn increase even more the secretion of inflammatory mediators such as TNF-α.…”
Section: Antipsychotics Glucose Intolerance Insulin Resistance and mentioning
confidence: 99%
See 1 more Smart Citation